Health-Related Quality of Life in Patients with COVID-19 in Indonesia: A Cross-Sectional Study - Fajriansyah, Fajriansyah; Lestari, Keri; Zulfahmidah, Zulfahmidah (Sciences of Pharmacy, 2026)
Evidence on health-related quality of life (HRQoL) among hospitalized COVID-19 patients in Indonesia remains limited, particularly during the acute phase of infection. This study aimed to describe HRQoL and its associated sociodemographic and clinical factors among hospitalized COVID-19 patients in Indonesia. A cross-sectional study was conducted among adult patients with polymerase chain reaction confirmed COVID-19 who were hospitalized at Rumah Sakit Darurat COVID-19 (RSDC) Wisma Atlet, Jakarta, between October - December 2021. HRQoL was assessed using the validated Bahasa Indonesia version of the EQ-5D-5L questionnaire, including the utility index derived from the Indonesian value set and the EQ visual analogue scale (EQ-VAS). Descriptive statistics were used to summarize HRQoL distributions, and group differences were analyzed using the Mann–Whitney U test and Kruskal–Wallis test. A total of 154 patients were included in the analysis. The mean EQ-5D-5L utility index was 0.762 (SD 0.23; 95% CI: 0.726–0.798), and the mean EQ-VAS score was 75.00 (SD 15.81; 95% CI: 72.48–77.52). Utility index values ranged from 0.311 to 1.000, with 31.17% of participants reporting full health. Among the EQ-5D-5L dimensions, anxiety/depression was the most frequently reported problem (68.83%). Statistically significant differences in utility index scores were observed across sex, age groups, and occupational status (p < 0.05). In conclusion, hospitalized COVID-19 patients in Indonesia reported moderately high overall HRQoL, while psychological problems particularly anxiety and depression were highly prevalent. These findings highlight the importance of integrating mental health support into inpatient care and recovery services.